KEBIJAKAN KRIMINAL TERHADAP KEKERASAN OLEH REMAJA (JUVENILE DELIQUENCY) DILIHAT DARI PERSPEKTIF SOSIO KRIMINOLOGIS - Ismawati, Sri; Lolita, Lolita (TANJUNGPURA LAW JOURNAL, 2021)
Abstract The phenomenon of violence by and against teenagers is often presented in the media causing a sense of concerns. Whereas teenagers are the potential next generation to continue the relay of state development. Therefore it is important for researchers to conduct a study and / or research on aetiology and the urgency of criminal policy related to it. This study is aimed at analyzing the problem of violence perpetrated by children - teenagers from the perspective of criminal policy and socio-criminology at the same time. Data from the police show that the dominant act of crime is theft by violence, persuasion, sexual coercion, murder, and assault, while the data obtained from Regional Indonesia Child Protection Commission (KPPAID) show the dominant act of crime are: physical, psychological and sexual abuse and abandonment. Given the impact, the government needs to prioritize criminal policies to tackle child violence, by using 2 (two) penal and non-penal approaches (symptomatic and therapeutic). The political perspective of child violence crime itself is a perspective that does not only see the problem of child violence as merely a criminal law issue but also tries to see the problem from a non-legal perspective. Criminal politics with a penal approach can be carried out by using criminal sanctions selectively, encouraging criminal alternatives that are oriented towards children's needs. Meanwhile, the non-penal approach aims at empowering the role of families, teachers, religious leaders, traditional leaders, and community leaders, empowering the education of perpetrators and victims related to the development aspects of children - teenagers, empowering the economy of the family and society at large, optimizing the role of the government and related institutions, and empowering the role of the family (education and sex education, and self-respect).Â Abstrak Fenomena kekerasan oleh dan terhadap anak kerap tersaji di media dan menimbulkan rasa prihatin. Padahal anak merupakan generasi penerus yang potensial guna meneruskan estafet pembangunan negara. Karenanya penting bagi peneliti melakukan sebuah kajian dan atau penelitian tentang aetiologi, urgensi kebijakan kriminal berkaitan dengan itu. Penelitian ini diarahkan untuk menganalisis persoalan kekerasan yang dilakukan oleh anak dari perspektif kebijakan kriminal dan sekaligus sosio kriminologis. Data kepolisian menunjukan dominasi kejahatan adalah pencurian dengan kekerasan, pembujukan, pemaksaan seksual, pembunuhan, penganiayaan. Data yang didapat dari KPPAID: penelantaran (ekonomi) kekerasan fisik, psikis, dan seksual. Mengingat dampak, pemerintah perlu mengedepankan kebijakan kriminal guna menanggulangi kekerasan anak, melalui 2 (dua) pendekatan, yaitu penal dan non penal (simptomatik dan teurapatik). Perspektif kebijakan kriminal kekerasan anak sendirimerupakan suatu perspektif yang tidak hanya melihat persoalan kekerasan anak sematamata sebagai persoalan hukum pidana saja, melain juga mencoba melihat persoalan dari perspektif non hukum. Kebijakan kriminal dengan pendekatan penal dapat dilakukan dengan penggunaan sanksi pidana secara selektif, mendorong alternatif pidana yang berorientasi pada kebutuhan anak. Sedangkan pendekatan non penal menyasar pada melakukan pemberdayaan peran keluarga, guru, pemuka masyarakat, adat dan agama, pemberdayaan pendidikan pelaku dan korban yang berkaitan dengan aspek perkembangan anak â€“ remaja, pemberdayaan ekonomi keluarga dan masyarakat secara luas, mengoptimalkan peran pemerintah baik pusat maupun daerah dan lembaga terkai pemberdayaan peran keluarga (edukasi dan edusex serta penghargaan diri sendiri),